Acute effects of exercise-induced muscle damage on sprint and change of direction performance: A systematic review and metaanalysis - Harrison, Drew C.; Doma, Kenji; Rush, Catherine; Connor, Jonathan (Biology of Sport, 2024)
The aim of this study is to determine the acute effects of resistance and plyometric training on sprint and change of direction (COD) performance in healthy adults and adolescents. A systematic literature search was conducted via Medline, Cinahl, Scopus and SportDiscus databases for studies that investigated: 1) healthy male, female adults, or adolescents; and 2) measured sprint or change of direction performance following resistance and plyometric exercises. Studies were excluded if: 1) resistance or plyometric exercises was not used to induce muscle damage; 2) conducted in animals, infants, elderly; 3) sprint performance and/or agility performance was not measured 24 h post muscle damaging protocol. Study appraisal was completed using the Kmet Quality Scoring for Quantitative Study tool. Forest plots were generated to quantitatively analyse data and report study statistics for statistical significance and heterogeneity. The included studies ( n = 20) revealed sprint and COD performance was significantly impaired up to 72 hr following resistance and plyometric exercises; both protocols significantly increased creatine kinase (CK), delayed-onset muscle soreness (DOMS) and decreased countermovement jump (CMJ) up to 72 hr. The systematic review of 20 studies indicated that resistance and plyometric training significantly impaired sprint and COD performance up to 72 hours post-exercise. Both training protocols elevated exerciseinduced muscle damage (EIMD) markers (CK, DOMS) and decreased CMJ performance within the same timeframe.